Doubtful records of reptile species in some areas of the Danube Delta Biosphere Reserve (Romania) - TÖRÖK Zsolt Csaba (Scientific Annals of the Danube Delta Institute, 2012)
In the present paper there are provided details on the doubtful data on the occurrence of some reptile species in various parts of the Danube Delta Biosphere Reserve. Testudo graeca was indicated by mistake at Sfântu Gheorghe (probably the authors saw the species in some places from the continental plateau nearby of Sfântu Gheorghe branch, not inside the Danube Delta). Lacerta viridis was mentioned in the so-called “maritime Delta” and at the ruins of Histria fortress (due to confusion with specimens of Lacerta agilis). Also, Podarcis muralis was “recorded” at the ruins of Histria fortress (due to misidentification of specimens belonging to species P. taurica. A corps of snake found at Letea forest was considered by mistake as belonging to species Eryx jaculus. In several official reports (grey literature) the species Elaphe longissima (Zamenis longissimus) was mentioned by mistake as occurring at Letea forest. Elaphe (quatuorlineata) sauromates was “recorded” at the ruins of Histria fortress and at Sfântu Gheorghe due to confusion with specimens belonging to other snake species. Specimens of Vipera urisnii from the Danube Delta were considered as belonging to the species Vipera berus. Also, Vipera ursinii was metioned by mistake at Caraorman marine levee and at Chituc marine levee, based only on the idea that if the species occurs on other marine levees, it has to be present on these two marine levees, too.